2013
DOI: 10.1016/j.jmaa.2012.08.048
|View full text |Cite
|
Sign up to set email alerts
|

Singularity and existence for a wave system of nematic liquid crystals

Abstract: Abstract. In this paper, we prove the global existence and singularity formation for a wave system from modelling nematic liquid crystals in one space dimension. In our model, although the viscous damping term is included, the solution with smooth initial data still has gradient blowup in general, even when the initial energy is arbitrarily small.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 15 publications
1
34
0
Order By: Relevance
“…As mentioned in Section 1.2, the two examples of finite time singularity formation constructed in [23] for the parabolic system over bounded regions are directly related to or caused by some non-trivial global/topological conditions. While as the singularity claimed in Theorem 1 is formed in essentially the same mechanism as that in [12,18] -it is created locally due to interactions of local waves that are of finite speed. A typical point singularity of direction field n of three dimensional parabolic system is in the form of x/|x|, which is not continuous at singular point.…”
Section: 23mentioning
confidence: 87%
See 4 more Smart Citations
“…As mentioned in Section 1.2, the two examples of finite time singularity formation constructed in [23] for the parabolic system over bounded regions are directly related to or caused by some non-trivial global/topological conditions. While as the singularity claimed in Theorem 1 is formed in essentially the same mechanism as that in [12,18] -it is created locally due to interactions of local waves that are of finite speed. A typical point singularity of direction field n of three dimensional parabolic system is in the form of x/|x|, which is not continuous at singular point.…”
Section: 23mentioning
confidence: 87%
“…Later this result was extended to more general initial data in [20], the case with damping in [12] and the variational wave system with n ∈ S 2 in [11,39,40]. Especially, in [12], the authors showed that behaviors of large solutions of the variational wave systems with and without damping are similar. The global well-posedness of Hölder continuous conservative solutions was established for the variational wave system, including: uniqueness [3,7], Lipschitz continuous dependence on some optimal transport metric [1], and generic regularity [2,5].…”
Section: 2mentioning
confidence: 88%
See 3 more Smart Citations